THE BRAIN THAT WOULDN'T DIE AND BOXING HELENA: DESIRE AND THE DISMEMBERMENT OF THE FEMALE BODY - Hardin, Michel (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 2001)
The author compares The Brain That Wouldn't Die, a 1960 B-movie with Jennifer Chambers Lynch's Boxing Helena (1993) in order to show how spectators not only take on the sadistic position which has long been thought to be the one position informing Hollywood cinema but tend to shift between different positions, including masochistic positions. Both movies relate the fetish fantasies of a doctor: in both narratives, the protagonists artificially maintain alive dismembered female bodies. In neither movie is the desire that produces these fetish fantasies clearly critiqued. To some extent, the Oedipal conflict might explain the sexual neuroses of the protagonists. However, both movies have the spectator shift the identification process from one character to the other. In Boxing Helena, such shifts in spectator identification are mirrored on the screen, creating a critique of film, film theory, and voyeurism.